Comparison And Optimization Of Ozone – Based Advanced Oxidation Processes In The Treatment Of Stabilized Landfill Leachate - Abuamro, Salem S. S. (2013)
Leachate pollution is one of the main problems in landfilling. Among the most problematic parameters in stabilized leachate are COD, ammonia, and color. The treatment technology that can be used may differ based on the type of leachate produced. Even after treatment, the effluent characteristics are always hard to comply with the discharge standard. Ozonation is one of the chemical processes that can be used in the treatment of landfill leachate. However, its performance when use alone is low; its effectiveness can be improved using advanced oxidants. To date, application of Fenton and persulfate reagents separately to improve ozonation process in one ozone reactor was not well established. The study aimed to evaluate and compare the performance of the three treatment processes, namely ozone, ozone/Fenton and ozone/persulfate in treating stabilized leachate separately at different experimental conditions. A central composite design (CCD) with response surface methodology (RSM) was applied to evaluate the relationships between operating variables. Based on statistical analysis, quadratic models for the four responses (COD, NH3–N, Color, and ozone consumption (OC)) proved to be significant with very low probability values (<0.0001). For the three optimization designs; the predicted results fitted well with the results of the laboratory experiment. This study also investigated the effects of the three treatment processes on the biodegradable and soluble characteristics of stabilized leachate. The biodegradability (BOD5/COD ratio) in stabilized leachate was 0.034, and it’s improved to 0.05, 0.14 and 0.29 by applying O3, O3/fenton and O3/persulfate, respectively.